Theoretical and Experimental Study of the Effects of Impact Drilling Parameters on the Properties of Surrounding Rock Damage - Zhi Liu; Wanrong Wu; Qianhua Hao; Peng Sun; Yuangen Ding (Shock and Vibration)
Using a self-designed hydraulic impact drilling test-bed and rock core drill, six groups of cylindrical granite specimens (93 mm dia. × 200 mm) containing central axial holes formed either by impact or nonimpact drilling methods were tested in uniaxial compression to failure on an Instron 1346 universal testing machine to investigate their mechanics and damage properties. The longitudinal acoustic wave velocities were measured before testing. The rock specimens were grouped according to the method of drilling the central hole (impact load exerted by different impact power and different frequencies for an approximately identical impact power, or nonimpact drilling). In this study, a statistical constitutive damage model based on Weibull distribution was used to calculate the degree of rock damage after drilling center holes. The experimental curves were measured to analyze the damage evolution process and the radius of rock damage. These indicate that rock damage increased with the increase of impact power and decreased with increasing impact frequency at constant impact power. This was also verified by the measured longitudinal wave velocity in all rock specimens. These results have significance for guiding the design of composite rock drilling tools that are dedicated to improving rock-breaking efficiency.